STUDI SISTEM INFORMASI GEOGRAFIS (SIG) BAGI PERENCANAAN PENGHIJAUAN DI KELURAHAN SATRIA KOTA TEBING TINGG - Andi Syahputra; Anita Zaitunah; Deni Elfiati (Peronema Forestry Science Journal, 2016)
There are some environmental problems in the development of urban areas including air, water and soil pollution. The high growth level of population which are followed by the establishment of industrial zones and settlements areas have cause less of vegetation areas. The purpose of this study was to identify areas which is potential to be developed as afforestation areas using geographic information systems by applications using SPOT 5 satellite imagey. Afforestation planning of bare land is in the form of afforestation in settlements areaswith total area of ​​7.14 hectares. Afforestation planning in the green belt is afforestation along roads and the river. There is 169.52 kilometers of road length to be afforested. Suitable plant species could be Pterocarpus indicus, Filicium decipiens, Polyalthia longifolia, Mimusops elengi, Switenia mahagoni, Casuarina equisetifolia, and Oreodoxa regia. Along the river bank of 17.27 kilometers length is recommended to be afforested with bamboo plants. Keywords: Reboisation Planning, SPOT 5 imagery, Geographic Information Systems (GIS)